The bigger the calf the better the cow true or false? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Calves often get only half of the milk produced by their mothers in African pastoral and agropastoral systems; the rest goes to the animals' owners. Up till now it had been thought that these calves, which are weaned when still small, would reach...